Baseline CSF phosphorylated tau as an indicator of subsequent tau accumulation on tau PET. (1st February 2022) - Cogswell, Petrice M; Wiste, Heather J.; Mielke, Michelle M.; Schwarz, Christopher G.; Weigand, Stephen D; Lowe, Val J; Therneau, Terry M.; Knopman, David S.; Graff‐Radford, Jonathan; Vemuri, Prashanthi; Senjem, Matthew L.; Gunter, Jeffrey L.; et al.
Abstract: Background: Alzheimer's disease biomarkers of tau pathology may be assessed by both CSF and PET. Cross‐sectional associations between CSF phosphorylated tau (p‐tau) and tau PET have been studied and regional tau PET SUVR has been shown to have similar diagnostic performance as CSF p‐tau. The association between CSF p‐tau and longitudinal tau PET has not been studied. CSF measures may be thought of as a result of the imbalance of influx vs efflux of soluble tau, whereas, tau PET reflects total tau accumulation into insoluble aggregates to date. We therefore hypothesize that baseline CSF p‐tau may be a leading indicator of future tau PET accumulation. Method: We identified Mayo Clinic Study of Aging (MCSA) and Mayo Alzheimer's Disease Research Center (ADRC) participants with diagnoses of cognitively unimpaired, mild cognitive impairment, and amnestic dementia who had CSF p‐tau (Elecsys p‐tau [181P]) and subsequent serial tau PET (flortaucipir) exams. The first tau PET scan was within 3 years of the CSF p‐tau collection. A longitudinal pipeline with two‐compartment partial volume correction was used to measure change in tau PET in a temporal‐lobe meta‐ROI (amygdala, fusiform, middle/inferior temporal, entorhinal, and parahippocampal regions) with a composite reference region (eroded supratentorial white matter, pons, and whole cerebellum). Spearman correlation was used to assess the association between CSF p‐tau and annual percent change in tau PET. A linear mixed effects model was fit to assess the association adjusting for age and sex. Result: The study included 143 participants (76% cognitively unimpaired) (). CSF p‐tau was significantly associated with annual percent change in tau PET overall (Spearman R=0.19, p=0.023) () and after adjusting for age and sex (p<0.001) (). There was nonlinearity in the CSF p‐tau effect, with higher values (>20 pg/mL) having a greater association with annual change in tau PET than lower values. Conclusion: In a group of cognitively unimpaired and impaired participants, CSF p‐tau predicted subsequent tau PET accumulation rate. A threshold effect is suggested with subsequent tau PET accumulation primarily in participants with elevated CSF p‐tau levels near the Mayo threshold of 22 pg/mL.